2021
DOI: 10.1080/19942060.2021.1934546
|View full text |Cite
|
Sign up to set email alerts
|

Using soft computing and machine learning algorithms to predict the discharge coefficient of curved labyrinth overflows

Abstract: This research aims to estimate the overflow capacity of a curved labyrinth using different intelligent prediction models, namely the adaptive neural-fuzzy inference system, the support vector machine, the M5 model tree, the least-squares support vector machine and the least-squares support vector machine-bat algorithm (LSSVM-BA). A total of 355 empirical data for 6 different congressional overflow models were extracted from the results of a laboratory study on labyrinth overflow models. The parameters of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Karami et al 10 showed that the ELM method with RMSE = 0.006 has acceptable efficiency in estimating the C d of the labyrinth weir. In a similar study, the effectiveness of the least-squares support vector machine-bat algorithm (LSSVM-BA) method was used to investigate the discharge of a curved labyrinth weir 39 . The results of the studies showed that the SVM-based model gave accurate results in estimating the C d of the arched labyrinth weir with values of RMSE = 0.013 and R 2 = 0.970 40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karami et al 10 showed that the ELM method with RMSE = 0.006 has acceptable efficiency in estimating the C d of the labyrinth weir. In a similar study, the effectiveness of the least-squares support vector machine-bat algorithm (LSSVM-BA) method was used to investigate the discharge of a curved labyrinth weir 39 . The results of the studies showed that the SVM-based model gave accurate results in estimating the C d of the arched labyrinth weir with values of RMSE = 0.013 and R 2 = 0.970 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the effective length of the labyrinths at a specified width, due to the radius increases of PCLW1 and PCLW2 weirs causes an increase in the Cd. The studies showed that increasing the radius causes a reduction in eddy flows, turbulence, and a sudden increase in water height during the weir 39 , 40 , 42 . The results of the investigations showed that with the increase of R/W, the C d increases in the arched labyrinth weir, which is consistent with the results of the present study 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Olyaie et al (2019) simulation indicated that the LSSVR could predict the Cd of the piano key (PK) weir accurately enough. The LSSVR was used to model the Cd of curved labyrinth overflows (Hu et al, 2021). They found that it could be a suitable tool for predicting Cd.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [17] conducted research on the surface wind pressure of low-rise buildings, obtained the surface wind pressure under different wind forces by using numerical simulation methods, established a surrogate model based on machine learning, and applied it to optimize the placement of building surface pressure sensors. Hu et al [18] used adaptive neural-fuzzy inference system, support vector machine, M5 model tree, least-squares support vector machine, and other intelligent prediction models to predict the overflow coefficient of curved pipelines, establishing the mapping relationship between the upstream water head, overflow ratio, curvature, and overflow coefficient. Wakes et al [19] used machine-learning algorithms to predict dune movement patterns under different wind conditions, providing a technical reference for predicting sediment migration paths.…”
Section: Introductionmentioning
confidence: 99%